Suppression of proatherogenic leukocyte interactions by MCS-18 - Impact on advanced atherosclerosis in ApoE-deficient mice - Kühn, Constanze; Tauchi, Miyuki; Stumpf, Christian; Daniel, Christoph; Bäuerle, Tobias; Schwarz, Marc; Kerek, Franz; Steinkasserer, Alexander; Zinser, Elisabeth; Achenbach, Stephan; Dietel, Barbara (Atherosclerosis, 2016)
Atherosclerosis is associated with chronic inflammatory responses of the arterial blood vessels. The previously observed protective effect of the MCS-18 substance against the initiation of atherosclerosis in a murine model was explained by its pronounced anti-inflammatory activity. Here, we investigated its impact on murine plaque progression in advanced atherosclerosis and on proatherogenic processes.ApoE-deficient mice were fed a high-fat diet for 12 weeks to induce atherosclerosis, followed by normal chow and intraperitoneal injections of either MCS-18 (500 ?g, n = 10) or saline (n = 10) twice a week for another 12 weeks. Plaque size was reduced in MCS-18 treated mice compared to controls (p = 0.001), which was associated with a reduced size of the lipid core (p = 0.01). There was a decrease in apoptotic cells (p = 0.02), endothelial ICAM-1 expression (p < 0.001), and macrophage density (p = 0.01) in the MCS-18 group. In addition, human and murine dendritic cells (DCs) and human umbilical vein endothelial cells (HUVECs) were treated with MCS-18 (50-200 ?g/ml) to analyze cell migration and adhesion under flow conditions. MCS-18 reduced human (p = 0.01) and murine (p = 0.006) DC migration. Furthermore, adhesion of MCS-18-treated DCs to a HUVEC monolayer was decreased (p < 0.001). Compared to controls, CD209 (p < 0.001) and CCR7 (p = 0.003) expression was decreased in MCS-18-treated DCs, while in HUVECs lower levels of ICAM-1 (p < 0.001) and of phosphorylated NF-?B-p65 (p = 0.002) were observed. Blocking of ICAM-1 reduced DC adhesion (p < 0.001).MCS-18 exhibits interesting therapeutic effects when applied in advanced murine atherosclerosis. Its antiatherogenic impact might be associated with a suppressed adhesion to the endothelium due to down-regulation of endothelial ICAM-1 expression.
EVALuna2:12031